Characteristics That Predict Psoriatic Arthritis by the Classification Criteria for Psoriatic Arthritis in Patients With Juvenile Idiopathic Arthritis 18 Years After Disease Onset - Agnes Szentpetery; Mia Glerup; Kristiina Aalto; Ellen D. Arnstad; Anders Fasth; Troels Herlin; Charlotte Myrup; Ellen Nordal; Suvi Peltoniemi; Marite Rygg; Veronika Gjertsen Rypdal; Lillemor Berntson (ACR Open Rheumatology)
Objective The purposes of this study were to assess the clinical characteristics of patients with juvenile idiopathic arthritis (JIA) who fulfill the ClASsification criteria for Psoriatic ARthritis (CASPAR) 18 years after disease onset in a population‐based setting and to identify features likely to predict psoriatic arthritis (PsA). Methods Patients with JIA from defined geographic regions of Denmark, Finland, Norway, and Sweden with disease onset from 1997 to 2000 were enrolled prospectively and followed up for 18 years. Clinical, laboratory, and heredity data for psoriasis were collected. Patients were classified according to the International League of Associations for Rheumatology (ILAR) criteria at baseline, and we applied ILAR and CASPAR criteria at 18 years. Logistic regression was performed to study the effects of JIA‐related characteristics and heredity for psoriasis on being classified for PsA. Results Among the 510 patients enrolled, 434 participated in the 18‐year follow‐up, 28 (6.5%) met the ILAR criteria, and 41 (9.4%) fulfilled the CASPAR criteria. Patients with wrist or subtalar joint involvement at onset had higher odds of being classified with PsA at 18 years (odds ratio [OR] 3.3, P = 0.02 and OR 12.9, P = 0.01, respectively). Presence of psoriasis, nail abnormalities, or dactylitis showed significant association with development of PsA (OR 20.2, P < 0.001; OR 11.6, P = 0.002; and OR 43.4, P < 0.001, respectively). Conclusion CASPAR criteria identify more patients with PsA compared with ILAR criteria and may better capture the heterogeneous nature of the disease. Presence of psoriasis and dactylitis at disease onset were the strongest predictors for the development of PsA. Further studies on the utility of CASPAR criteria in patients with JIA are needed.